SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN JUMLAH BERAS MISKIN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHT (SAW) - Dewi Angrawati; Muh. Yamin; Natalis Ransi (semanTIK, 2016)
Ricefor the poor program, known as  Raskin  is one of the government programs to reduce expenditure and the protection of poor families through the distribution of rice with a number and a specified price .in the distribution of Raskin often encountered obstacles or problems, one of them for leveling Raskin  amount received by all recipients Raskin. While there are different social degrees between the receiver  Raskin.  Raskin  distribution given the same amount to all recipients  Raskin, happens because it is still done manually allowing the occurrence of a subjective determination by the village government because it has not referring to predetermined criteria. In this study used methods of SAW  (Simple Additive Weight). SAW weighted summation , namely by finding a weighted sum of the value of the performance of each alternative on all attributes and requires a decision matrix normalization process (X) to a scale which can be compared with all existing alternatives value. The results of this analysis, a decision support system determines the amount of rice for the poor (Raskin ) using Simple Additive Weight (SAW)  in the village Puupi, Kolono, Southern Konawe district. The analysis is given based on the normalized matrix multiplication and summation with weights. Keywords—Decision Support System, Simple Additive Weight (SAW), Raskin